(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
We consider performance and initiation’s rituals with respect to the tortoise game (chelichelṓnē). At first, Julius Pollux, the second-century CE lexicographer, describes the game, to wich Erinna in her lost poem “The Distaff” and Eustathius also refer. This was a game for girls of marriageable age and it was performed, in order to instruct them to their future status as wives and mothers. As Pollux states, the cauldron game (chytrinda) was the exact counterpart of the chelichelṓnē for young boys. Finally, the deep social and religious meaning of these games, including performatory elements, such as dance, nursery rhymes, and ritual acts, is to be scrutinized, in order to better understand these rites of transition into the world(s) of adults.